Effect of resin uptakes from Acacia mangium on the surface properties of impregnated paper from Tannin phenol formaldehyde - Mohammad Noh, Nurul Farhana (2016)
Acacia mangium is a fast-growing dicotyledonous tree species and has become the dominating plantation in Malaysia. It was grown particularly as a raw material for veneer, pulp and paper industries. The chemical properties test in this study showed that the A. mangium tree bark contains higher extractive content as compared to the wood portion (sapwood). In this study, the solution with 30%± solid content was extracted from Acaica bark. The aim of this work was to determine the effect of resin uptakes on the surface properties of impregnated paper. Tannin has potential to be used as a good bonding agent due to their polyphenolic structure. Source of tannin can be found in various type of tree bark such as mangrove, Acacia (A.mangium), mimosa (Acacia mearnsii), quabracho ( Schinopsis balansae) and pine ( Pinus radiate). Tannin (30% solid content) was mixed with phenol formaldehyde (PF) resin at three resin uptakes (250g/m2, 300g/m2, 350g/m²), then impregnated into filter paper. The impregnate paper was putted it onto the plywood and pressed under temperature of 180ºC for 7 minutes. Impregnated papers were cutting into dimension according to TAPPI, (1996) for testing. The type of testing is water vapour resistance, cross-cut test and mark stain test. The result showed that, the surface quality on paper laminate is applicable and proven by the water vapour testing.